SEMA6B-related progressive myoclonus epilepsy in a patient with Klinefelter syndrome - T. V. Kozhanova; S. S. Zhilina; T. I. Meshcheryakova; L. M. Sushko; K. V. Osipova; A. M. Mazur; S. S. Fomenko; A. I. Krapivkin; N. N. Zavadenko (Эпилепсия и пароксизмальные состояния)
In most cases, variants of nucleotide sequence in the SEMA6B gene account for developing the phenotype of progressive myoclonus epilepsy and, to a lesser extent, developmental encephalopathy with or without epilepsy. Loss-of-function variants in nucleotide sequence localized mainly in exon 17 of the SEMA6B gene contribute to production of aberrant proteins with “toxic” functions. A clinical case of status epilepsy in a patient with a variant in the SEMA6B gene (c.2506delС; p.His836ThrfsTer136; NM_032108.4) is described in the article that expands our knowledge regarding the SEMA6B gene variants resulting in progressive myoclonus epilepsy.